2006
DOI: 10.1016/j.bbabio.2005.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide binding and thermal stability of photosystem II isolated from Thermosynechococcus elongatus

Abstract: Binding of herbicides to photosystem II inhibits the electron transfer from Q(A) to Q(B) due to competition of herbicides with plastoquinone bound at the Q(B) site. We investigated herbicide binding to monomeric and dimeric photosystem II core complexes (PSIIcc) isolated from Thermosynechococcus elongatus by a combination of different methods (isothermal titration and differential scanning calorimetry, CD spectroscopy and measurements of the oxygen evolution) yielding binding constants, enthalpies and stoichio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…5B). The previous observation that bromoxynil and ioxynil showed endothermic binding reactions in contrast to exothermic binding of other herbicides (Zimmermann et al 2006) seems to be consistent with deprotonation of phenolic OH upon binding to PSII. D1-His215, which is a ligand to the non-heme iron, has been proposed to interact with phenolic herbicides (Oettmeier 1999;Sobolev and Edelman 1995;Trebst 1987Trebst , 1996.…”
Section: Discussionmentioning
confidence: 75%
“…5B). The previous observation that bromoxynil and ioxynil showed endothermic binding reactions in contrast to exothermic binding of other herbicides (Zimmermann et al 2006) seems to be consistent with deprotonation of phenolic OH upon binding to PSII. D1-His215, which is a ligand to the non-heme iron, has been proposed to interact with phenolic herbicides (Oettmeier 1999;Sobolev and Edelman 1995;Trebst 1987Trebst , 1996.…”
Section: Discussionmentioning
confidence: 75%
“…A weaker electron density (compared to Q A ) was observed for the mobile quinone Q B . Based on this diminished electron density and biochemical/biophysical evidence (see Kern et al 2005a, b;Zimmermann et al 2006) the occupancy of the Q B site was estimated to be about 50%. The positioning in the Q B pocket allows hydrogenbonding interactions between the keto-oxygens of the PQ9 and D1-Ser264Oc and the nitrogens Ne of His215 and of the backbone amide of Phe265, respectively (Ferreira et al 2004;Loll et al 2005).…”
Section: Structure Of the Psii Acceptor Sidementioning
confidence: 99%
“…In-depth characterization of the protein samples as well as investigations on the physical chemistry of the bound cofactors provided a detailed knowledge that was used to improve crystal quality in terms of growth conditions of the cyanobacterium T. elongatus, protein isolation, and crystallization conditions Zouni et al 2005;Zimmermann et al 2006). The obtained structural model at 3.0 Å resolution ) revealed many novelties concerning the cofactor inventory and uncovered mis-interpretations of previous structural models at lower resolution.…”
Section: Introductionmentioning
confidence: 97%
“…They all crystallized PSII from different thermophilic cyanobacteria, because it was expected that these complexes would be more stable compared to plant PSII and therefore more suitable for crystallization trials. Recently it was indeed shown that PSII from Thermosynechococcus elongatus is heat stable with a melting temperature of 70°C as determined by differential scanning calorimetry (Zimmermann et al 2006). This value is 25°C higher than the one determined for spinach PSII (45°C, K. D. Irrgang, A.…”
Section: Introductionmentioning
confidence: 98%